An analysis of the gene complement of a marsupial, Monodelphis domestica: Evolution of lineage-specific genes and giant chromosomes - Goodstadt, Leo (Cold Spring Harbor Laboratory Press, 2007)
The newly sequenced genome of Monodelphis domestica not only provides the out-group necessary to better understand our own eutherian lineage, but it enables insights into the innovative biology of metatherians. Here, we compare Monodelphis with Homo sequences from alignments of single nucleotides, genes, and whole chromosomes. Using PhyOP, we have established orthologs in Homo for 82% (15,250) of Monodelphis gene predictions. Those with single orthologs in each species exhibited a high median synonymous substitution rate (d(S) = 1.02), thereby explaining the relative paucity of aligned regions outside of coding sequences. Orthology assignments were used to construct a synteny map that illustrates the considerable fragmentation of Monodelphis and Homo karyotypes since their therian last common ancestor. Fifteen percent of Monodelphis genes are predicted, from their low divergence at synonymous sites, to have been duplicated in the metatherian lineage. The majority of Monodelphis-specific genes possess predicted roles in chemosensation, reproduction, adaptation to specific diets, and immunity. Using alignments of Monodelphis genes to sequences from either Homo or Trichosurus vulpecula (an Australian marsupial), we show that metatherian X chromosomes have elevated silent substitution rates and high G+C contents in comparison with both metatherian autosomes and eutherian chromosomes. Each of these elevations is also a feature of subtelomeric chromosomal regions. We attribute these observations to high rates of female-specific recombination near the chromosomal ends and within the X chromosome, which act to sustain or increase G+C levels by biased gene conversion. In particular, we propose that the higher G+C content of the Monodelphis X chromosome is a direct consequence of its small size relative to the giant autosomes.